PENGARUH KEPRIBADIAN OTORITARIAN, KEPUASAN GAJI DAN BUDAYA ORGANISASI POLISI TERHADAP TINDAK KORUPSI DI LEMBAGA KEPOLISIAN - RAHMI BS, SITA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Corruption was considered as white collar crime. The dominant effect of corruption mainly implied collective poverty in many countries. In fact, the practice of corruption also took place in police institution that actually should enforce the law especially corruption alleviation. Abuse of power, law salary and ineffective control were considered as the causes of corruption in many institutions. Therefore, this research aims at identifying the influence of authoritarian personality, pay satisfaction and police organizational culture on the practice of corruption among police officers. This research design incorporated survey and questionnaire instrument with four scales. The research was conducted in the region of Sleman police institution with 160 respondents. Regression test was used to analyze the responses collected from the surveys done. The hypotheses test resulted authoritarian personality (p=0,005 (p<0,05)) and police organizational culture (p= 0,021 (p<0,05)) influenced police corruption significantly. Meanwhile, pay satisfaction was not verified as a cause of police corruption at all (p=0,215 (p>0,05). Besides, an additional test with T test indicates that there was no different level of corruption, authoritarian personality and pay satisfaction in respondents group with different ages. There was no different of corruption tension and pay satisfaction of the respondents with high salary or the lower one. Meanwhile, the majority of the respondents (70,6%) in this research were categorized as potentially corrupt in the mid-level. Keywords: Police corruption, authoritarian personality, pays satisfaction, police organizational culture